Strategi Mempertahankan Kearifan Lokal Seni Kriya Wayang Pada Pengrajin Wayang Kulit di Desa Sonorejo - Darin Alya Husniyah; Bagas Narenda Parahita; Danang Purwanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Local wisdom is an identity inherent in Indonesian society. This research aims to determine the obstacles and strategies for maintaining the local wisdom of craft arts among shadow puppet craftsmen. The approach in this research is descriptive qualitative research. The research location was carried out in Sonorejo Village, Sukoharjo Regency. The results of the research show that the existence of obstacles encourages craftsmen to strive for strategies to preserve local wisdom in the form of wayang kulit. These obstacles come in the form of economic factors and the declining interest of the younger generation. Then, craftsmen carry out strategies to overcome these obstacles by introducing shadow puppetry as early as possible, joining organizations and communities, establishing puppet studios, and finding out trends in interest. The rational choice theory perspective proposed by James Coleman contains two micro elements, namely actors and resources. Thus, the dynamics of the regeneration decisions of shadow puppet craftsmen in Sonorejo Village are influenced by various factors so that shadow puppet craftsmen strive to maintain regeneration by adjusting the economic situation.